2016
DOI: 10.18632/oncotarget.13872
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage production and activation are dependent on TRIM33

Abstract: The tripartite motif (TRIM) family of proteins plays important roles in innate immunity and antimicrobial infection. None of these proteins has been shown to directly regulate transcription of genes in monocyte/macrophage except TRIM33 that we have recently shown to be a macrophage specific transcriptional inhibitor of Ifnb1. Using ChIP-seq analyses, we now report that TRIM33 is bound to two fold more genes in immature than in mature myeloid cell lines. When located near the same genes, TRIM33 is bound to diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 34 publications
(46 reference statements)
3
29
0
Order By: Relevance
“…Regarding the innate immune system, TIF1γ directly represses the transcription of the interferon-b gene ( ifnb ) at late phase of macrophage activation ( 74 ). Also, it binds multiple chromatin sites in monocyte to promote production of macrophage, binds other chromatin sites in mature macrophage to regulate the responses after toll-like receptor (TLR) activation by lipo-polysaccharide (LPS) ( 111 ), and is directly involved in proteasome activation via the ubiquitination of DHX33 ( 112 ). TIF1γ also has many roles in cell homeostasis; TIF1γ is strongly involved in antiproliferative cellular effect by (i) mediating ubiquitination and then the degradation of LIM-domain-binding protein which is involved in the transcription of cycle activator genes ( 113 ) and (ii) interaction with APC/C (anaphase-promoting complex/cyclosome) to promote the alignment and stability of chromosomes during mitosis and to prevent abnormal metaphase–anaphase transition ( 75 , 76 ).…”
Section: Targets Of Cancer-associated Autoimmune Response In Myositismentioning
confidence: 99%
“…Regarding the innate immune system, TIF1γ directly represses the transcription of the interferon-b gene ( ifnb ) at late phase of macrophage activation ( 74 ). Also, it binds multiple chromatin sites in monocyte to promote production of macrophage, binds other chromatin sites in mature macrophage to regulate the responses after toll-like receptor (TLR) activation by lipo-polysaccharide (LPS) ( 111 ), and is directly involved in proteasome activation via the ubiquitination of DHX33 ( 112 ). TIF1γ also has many roles in cell homeostasis; TIF1γ is strongly involved in antiproliferative cellular effect by (i) mediating ubiquitination and then the degradation of LIM-domain-binding protein which is involved in the transcription of cycle activator genes ( 113 ) and (ii) interaction with APC/C (anaphase-promoting complex/cyclosome) to promote the alignment and stability of chromosomes during mitosis and to prevent abnormal metaphase–anaphase transition ( 75 , 76 ).…”
Section: Targets Of Cancer-associated Autoimmune Response In Myositismentioning
confidence: 99%
“…Deficiency of TRIM33 in mature myeloid cells increased the expression of a subset of known LPS-repressible genes, whereas the expression of only few LPS-inducible genes was decreased. 92 In addition, studies in mice showed that TRIM33 and TRIM28 play a crucial role in the differentiation of Th17 cells. The knockout of TRIM33 or TRIM28 in CD4 + T cells reduced the expression of IL17 and IL17F but had, in contrast to the BET protein-regulated inhibition of Th17 differentiation, no effect on Th17-related transcription factors such as RORC.…”
Section: Introductionmentioning
confidence: 99%
“…The tripartite-motif family (TRIM) of proteins plays essential roles in the innate immune responses to antimicrobial infections. TRIM33, a member of the TRIM family and previously known as transcriptional intermediary factor 1 gamma (TIF1-γ), functions in monocyte/macrophage mediated inflammation (Gallouet et al, 2017 ) and inflammasome activation (Weng et al, 2014 ). Our results provided the first evidence of multiple differentially up-regulated immune-related proteins associated with protein ubiquitination in response to PS infection in Mv.1.Lu cells, indicating that ubiquitination appeared to be a pivotal regulatory mechanism in the immune responses to CDV infection in mink.…”
Section: Discussionmentioning
confidence: 99%